An enterohaemorrhagic Escherichia coli outbreak spread through the environment at an institute for people with intellectual disabilities in Japan in 2005 - Masaki Ota; Taro Kamigaki; Satoshi Mimura; Kazutoshi Nakashima; Takashi Ogami (World Health Organization Regional Office for the Western Pacific, 2019)
Objective: An enterohaemorrhagic Escherichia coli (EHEC) outbreak at an institute with multiple facilities for children and adults with intellectual disabilities was investigated to characterize the cases and identify risk factors for infection. Methods: A case was defined as a resident, a staff member or a visitor at the institute from 16 May through 30 June 2005 testing positive for type 2 Vero toxin-producing EHEC O157:H7 (confirmed case) or exhibiting bloody diarrhoea for two or more days (probable case). We collected and analysed demographic, clinical, laboratory and individual behaviour data to identify possible risk factors for infection and infection routes. Results: We recorded 58 confirmed cases, of which 13 were symptomatic. One probable case was also found. The median age of the patients was 37 years (range: 6-59 years). Thirty-six patients (61%) were male. Thirteen patients (93%) had diarrhoea and six (43%) had abdominal pain. Two developed haemolytic-uraemic syndrome but recovered. All the patients were treated with antibiotics and tested negative after treatment. Some residents had problems with personal hygiene. The residents of one of the facilities who cleaned a particular restroom had 18.0 times higher odds of being infected with EHEC (95% confidence interval: 4.0-102.4) than those who did not. Discussion: The source of the outbreak could not be identified; however, the infection may have spread through environmental sources contaminated with EHEC. We recommend that institutional settings, particularly those that accommodate people with intellectual disabilities, clean restrooms as often as possible to reduce possible infection from contact with infected surfaces.